2015
DOI: 10.1371/journal.pone.0117511
|View full text |Cite
|
Sign up to set email alerts
|

PE859, a Novel Tau Aggregation Inhibitor, Reduces Aggregated Tau and Prevents Onset and Progression of Neural Dysfunction In Vivo

Abstract: In tauopathies, a neural microtubule-associated protein tau (MAPT) is abnormally aggregated and forms neurofibrillary tangle. Therefore, inhibition of the tau aggregation is one of the key approaches for the treatment of these diseases. Here, we have identified a novel tau aggregation inhibitor, PE859. An oral administration of PE859 resulted in the significant reduction of sarkosyl-insoluble aggregated tau along with the prevention of onset and progression of the motor dysfunction in JNPL3 P301L-mutated human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 47 publications
(45 reference statements)
0
38
0
Order By: Relevance
“…In the A␤ 1-42 ELISA kit, anti-A␤ antibodies clone no. BNT77, which detects A␤ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , and clone no. BC05, which detects Cterminus of A␤ , were used.…”
Section: Enzyme-linked Immunosorbent Assay For Amyloid-βmentioning
confidence: 99%
See 1 more Smart Citation
“…In the A␤ 1-42 ELISA kit, anti-A␤ antibodies clone no. BNT77, which detects A␤ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] , and clone no. BC05, which detects Cterminus of A␤ , were used.…”
Section: Enzyme-linked Immunosorbent Assay For Amyloid-βmentioning
confidence: 99%
“…Previously, we introduced the novel tau aggregation inhibitor PE859 [15]. This compound is a curcumin derivative that we designed and synthesized to be a dual inhibitor of A␤ and tau aggregation [16].…”
Section: Introductionmentioning
confidence: 99%
“…has been shown to inhibit in vitro tau aggregation and to delay the onset and progression of motor dysfunction in vivo [38]. Moreover, 1,2-dihydroxybenzene-containing compounds have been shown to reduce tau oligomerization [39] in vitro or in vivo.…”
Section: Tau Aggregation Inhibitormentioning
confidence: 99%
“…As a result of screening of curcumin derivatives selected from a library on the basis of similarity in chemical structure to CU6/CNB-001, we found that GT863 reduced production of both Aβ40 and Aβ42. Interestingly, GT863 (formerly referred to as PE859) has been reported to inhibit Aβ and tau aggregation, and to ameliorate cognitive dysfunction, in AD mice models [15][16][17]. Although it has thus been shown that GT863 has beneficial effect in terms of suppressing Aβ aggregation, we were aware of no evidence indicating whether GT863 might suppress Aβ production.…”
mentioning
confidence: 92%
“…It should be noted that the low solubility in water and poor bioavailability of curcumin have limited its use in clinical trials and in therapeutic applications [6,12]. We were therefore interested in studying whether derivatives of curcumin could be found which might be more effective in treatment of AD than curcumin itself.Although curcumin derivatives have been the focus of studies seeking to develop inhibitors of Aβ and tau aggregation, and have been the focus of studies seeking to develop imaging probes for detection of Aβ and tau fibrils, there has been very little investigation into whether curcumin derivatives might serve as inhibitors of Aβ production [13][14][15][16][17][18][19]. We previously developed a series of curcumin derivatives and evaluated their inhibitory effects on Aβ production.…”
mentioning
confidence: 99%